Audit Delay dan Faktor-faktor yang Mempengaruhinya(Studi Empiris pada Perusahaan Manufakturyang Terdaftar di Bursa Efek Indonesia tahun 2011-2014) - Rahmawati, Zidny; , Drs.M.Abdul Aris,M.Si (2016)
The Purpose of this research is to know are size, profitability, leverage, audit opinion, KAP, and auditor switching constitute of factors which influence of the audit delay at manufacturing companies registered in Indonesian Stock Exchange. The population is manufacturing company listed in Indonesian Stock Exchange in 2011 to 2014. Sampling technique employed is Purposive Sampling with the total sample of 152 companies. Analytical technique used in this research is analysis of multiple linier regression.The result shows that leverage is constitute of factor which influence of audit delay, while size, provitability, auditor's opinion, size of public accountant, and auditor switching aren't constitute of factors which influence of audit delay.